“That’s Opuntia, that was!”, again: a new combination for an old and enigmatic Opuntia s.l. (Cactaceae) - Köhler, Matias; Font, Fabián; Puente-Martinez, Raul; Majure, Lucas Charles (Phytotaxa, 2021)
The genus Opuntia is one of the most emblematic of the cactus family (Cactaceae) and a species-rich clade within subfamily Opuntioideae. After molecular phylogenetic studies showed that the traditional broad circumscription of Opuntia could not be retained as the genus was polyphyletic, various segregated genera were recognize based on both morphological data and phylogenetic studies. Here, we reassessed an old and enigmatic taxon, O. schickendantzii, through molecular and morphological investigations. Our results support that O. schickendantzii was best circumscribed within the Salmonopuntia lineage based on molecular and morphological features. As a consequence, a new combination is proposed, and an epitype from the herbarium BAF is designated. An updated description of the taxon with illustrations is also given.